Analisis Pengaruh Pembiayaan Murabahah, Mudharabah dan Musyarakah Terhadap Profitabilitas Bank Umum Syariah di Indonesia pada Periode 2021-2024 - Solihah, Maratus; Syaefudin, Syaefudin; Cahaya Azwari, Peny (As-Syirkah: Islamic Economic & Financial Journal, 2026)
This study aims to analyze the effect of murabahah, mudharabah, and musyarakah financing on the profitability of Islamic commercial banks in Indonesia during the period 2021–2024. This research employs a quantitative approach. The population of this study includes Islamic Commercial Banks (ICBs) in Indonesia registered with the Financial Services Authority (OJK) during the 2021–2024 period, and purposive sampling was used to select a sample of 12 ICBs. The results indicate that murabahah, mudharabah, and musyarakah financing have a positive and significant effect on the profitability of Islamic commercial banks in Indonesia during the study period. Individually, each type of financing increases bank profitability, with musyarakah contributing the most. Simultaneously, these three types of financing explain 99.3% of the variation in profitability, indicating that effective management of Islamic financing can serve as an efficient strategy to enhance the financial performance of Islamic commercial banks in Indonesia.